Implikasi Perubahan Pengaturan Badan Usaha Milik Negara Indonesia Terhadap Relasi Negara Dengan Badan Usaha Milik Negara - Bahrul Ilmi Yakup (Universitas Sriwijaya, 2018)
State Owned Enterprise (SOE) is a strategic business entity in Indonesia, or in other countries. Since 1945, laws on Indonesia SOE had been changed 4 times, in four periods namely, 1945-1960 period, 1960-1969 period, 1969-2003 periode, and 2003-now. The law change has been driven Indonesia’s SOE concentrates on two principles profitable and cost-benefit recovery principles. The law change has caused loosened relation pattern between Indonesia state with SOE, then the Indonesia’s SOE metamorphed into commercial business entity.